Hypoplastic left heart syndrome: a review - Gobergs, Roberts; Salputra, Elza; Lubaua, Ingūna (Acta medica Lituanica, 2016)
Background. Hypoplastic left heart syndrome (HLHS) is an etiologically multifactorial congenital heart disease affecting one in 5,000 newborns. Thirty years ago there were no treatment options for this pathology and the  natural course of the  disease led to death, usually within the  first weeks of life. Recently surgical palliative techniques have been developed allowing for a five-year survival in more than half the cases. Materials and methods. We reviewed literature available on HLHS, specifically its anatomy, embryology and pathophysiology, and treatment. The  Pubmed and ClinicalKey databases were searched using the  key words hypoplastic left heart syndrome, foetal aortic valvuloplasty, foetal septoplasty, Norwood procedure, bidirectional Glenn procedure, Fontan procedure, hybrid procedure. The relevant literature was reviewed and included in the article. We reported a case from Children’s Clinical University Hospital, Riga, to illustrate treatment tactics in Latvia. Results. There are three possible directions for therapy in newborns with HLHS: orthotopic heart transplantation, staged surgical palliation and palliative non-surgical treatment or comfort care. Another treatment mode – foetal therapy – has arisen. Staged palliation and full Fontan circulation is a temporary solution, however, the only means for survival until heart transplantation. Fifty to 70% of patients who have gone through all three stages of palliation live to the age of five years. Conclusions. The  superior mode of treatment is not yet clear and the management must be based on each individual case, the experience of each clinic, as well as the financial aspects and will of the patient’s parents.
Keywords: hypoplastic left heart syndrome; Norwood procedure; bidirectional Glenn procedure; Fontan procedure; hybrid procedure; balloon valvuloplasty